AMPK in cardiovascular health and disease - Shirwany Najeeb A; Zou Ming-Hui (Acta Pharmacologica Sinica, 2016)
Adenosine Monophosphate-activated Protein Kinase (AMPK), a serine/threonine kinase and a member of the Snf1/AMPK protein kinase family, consists of three protein subunits that together make a functional enzyme. AMPK, which is expressed in a number of tissues, including the liver, brain, and skeletal muscle, is allosterically activated by a rise in the AMP: ATP ratio (ie in a low ATP or energy depleted state). The net effect of AMPK activation is to halt energy consuming (anabolic) pathways but to promote energy conserving (catabolic) cellular pathways. AMPK has therefore often been dubbed the “metabolic master switch”. AMPK also plays a critical physiological role in the cardiovascular system. Increasing evidence suggest that AMPK might also function as a sensor by responding to oxidative stress. Mostly importantly, AMPK modulates endogenous antioxidant gene expression and/or suppress the production of oxidants. AMPK promotes cardiovascular homeostasis by ensuring an optimum redox balance on the heart and vascular tissues. Dysfunctional AMPK is thought to underlie several cardiovascular pathologies. Here we review this kinase from its structure and discovery to current knowledge of its adaptive and maladaptive role in the cardiovascular system.